Validity of three commercial devices for recording movement velocity in the Bulgarian split squat - Chen, Z.; Liao, K.; Bishop, C.; Bian, C.; Li, Y. (Journal of Human Kinetics, 2025)
This study aimed to assess the validity of three commercial devices in recording mean velocity (MV) and peak velocity (PV) during a unilateral resistance exercise. Eighteen strength-trained and healthy males performed repetitions of Bulgarian split squats at loads ranging from 40% to 90% of their one-repetition maximum. MV and PV were simultaneously recorded by GymAware, PUSH, My Lift and compared to Vicon for all repetitions. Concurrent validity was assessed through a linear mixed model, as well as mean difference (MD), mean absolute error (MAE) and Hedge`s g effect sizes. GymAware was found to be valid in MV (MD = -0.02 to -0.01 m/s, MAE = 0.02 to 0.03 m/s, g = -0.08 to -0.19) and PV (MD = 0.01 to 0.05 m/s, MAE = 0.05 to 0.07 m/s, g = -0.06 to -0.22) recordings. Significant differences were identified between GymAware, PUSH, My Lift and Vicon for both MV (p < 0.01) and PV (p < 0.01) assessments. Moreover, when comparing MV and PV recorded by PUSH and My Lift to Vicon, larger MD and MAE, and trivial to moderate effects were also evident. Therefore, our findings suggest that GymAware could be an alternative for recording MV and PV during unilateral resistance exercises.